Utilizing Frémy's Salt to Increase the Mechanical Rigidity of Supramolecular Peptide-Based Gel Networks - Fichman, Galit; Schneider, Joel P. (Frontiers in Bioengineering and Biotechnology, 2021)
Peptide-based supramolecular gels are an important class of biomaterials that can be used for biomedical applications ranging from drug delivery to tissue engineering. Methodology that allows one to readily modulate the mechanical properties of these gels will allow yet even a broader range of applications. Frémy’s salt is an inorganic salt and long-lived free radical that is known to oxidize phenols. Herein, we show that Frémy’s salt can be used to dramatically increase the mechanical rigidity of hydrogels formed by tyrosine-containing self-assembling β-hairpin peptides. When Frémy’s salt is added to preformed gels, it converts tyrosine residues to o-quinones that can subsequently react with amines present within the lysine side chains of the assembled peptide. This results in the installation of chemical crosslinks that reinforce the gel matrix. We characterized the unoxidized and oxidized gel systems using UV-Vis, transmission electron microscopy and rheological measurements and show that Frémy’s salt increases the gel rigidity by nearly one order of magnitude, while retaining the gel’s shear-thin/recovery behavior. Thus, Frémy’s salt represents an on-demand method to modulate the mechanical rigidity of peptide-based self-assembled gels.